Advances in soilless cultivation technology of horticultural crops: Review - GAUTAM, RAVI; SINGH, P K; KUMAR, PRABHAT; R, SELVAKUMAR; SINGH, M C; DHITAL, SUSHIMA; RANI, MONIKA; SHARMA, V K; H, JNAPIKA K; KUMAR, JUGENDER (The Indian Journal of Agricultural Sciences, 2021)
The burgeoning population and climate change posing a challenge to meet the sufficient and quality food, fodder and fuel demand in 2050.The cultivable land is also shrinking due to industrialization and urbanization as the availability was 0.50 ha in 1960 which has come down at 0.25 ha. The continuous intensive agriculture led to poor soil health. The demand of food, fodder and fuel is ever rising with rise in population therefore; it is very difficult to sustain supply with present cultivation practices under climate change regime. To overcome this problem, soilless culture is one of the best alternatives. Soilless culture is a novel methodology for growing of crops or plants without soil by using growing media which can be solid, liquid, organic or inorganic material. One of the major advantages of soilless media is saving of water up to 85-90%, as water is recycled and provide better yield as compared to conventional cultivation with almost zero environmental pollution. Plug tray nursery raising using soilless medium is being done on commercial scale at many places. Research on Soilless cultivation is being carried out at Indian Agricultural Research Institute, Pusa, New Delhi since 2016. Hydroponic has been emerged as a new technique to grow plants in recent era. Aeroponics is one of the most successful and rapid methods of seed potato production in which large numbers of mini tubers can be produced in one generation which reduces time and cost. Plants grown in soil less culture are of superior quality with high yield, rich in nutrient content and rapid harvest as compared to conventional cultivation/soil. The growing conditions are generally regulated resultantly a robust resilient production system may be developed for continued supply of vegetables/fruits/flowers, it can synergistically add in total production.